Lung cancer mortality in European men and women : trends and predictions - T. Rosso; M. Malvezzi; P. Bertuccio; C. La Vecchia; C. Bosetti; E. Negri (2013)
Lung cancer mortality in men has been declining since the late 80's in most European countries, while mortality in women - although lower than in men - is still on the rise. To monitor the current lung cancer epidemic in European men and women, we analyzed mortality trends in 33 European countries between 1970 and 2009 and estimated rates for the year 2015 using data from the World Health Organization. Lung cancer mortality rates in EU men continued to fall over recent years. A favorable trend is thus likely to be maintained in the foreseeable future, although the predicted overall EU rate in 2015 is still over 35/100,000, i.e., higher than the US rate in 2007 (33.7/100,000). Female lung cancer mortality has been increasing up to recent calendar years in most European countries, with the exceptions of Belarus, Russia, and Ukraine, with relatively low rates, and the UK, Iceland and Ireland, where high rates were reached in mid/late 1990s to leveled off thereafter. A further increase is predicted, to reach 14/100,000 women in 2015. Widespread measures for smoking control and cessation in middle-aged Europeans, i.e., in the generations where smoking prevalence used to be high, would lead to appreciable reductions in lung cancer mortality in the near future. This is particularly urgent in central and eastern European countries. Although the female lung cancer epidemic in Europe is still expanding, the epidemic may be controlled through the implementation of effective anti-tobacco measures, and it will probably never reach the top US rates.